Beta-d-glucan-based drug delivery system and its potential application in targeting tumor associated macrophages. (1st February 2021) - Su, Yuting; Chen, Lei; Yang, Fan; Cheung, Peter C.K.
Highlights: β-glucans can be specifically recognized by immune cells like macrophages. Cancer immunotherapy based on TAMs profile in TME is an emerging strategy with its unique merits. β-glucans have the potential use as nano-carrier for drug delivery targeting TAMs. Abstract: Use of polysaccharides as carriers in drug delivery system is a hot topic, especially those with specific recognition of immune cells, enabling them to be applied in targeting delivery system. β-d -glucans are naturally occurring non-digestible polysaccharides with immunomodulatory activities that have attracted increasing attention to serve as therapeutic agents or immune-adjuvants. Being able to be specifically recognized by immune cells like macrophages, β-d -glucans can be developed as promising carriers for targeting delivery with stability, biocompatibility and specificity when applied in immunotherapy. Targeting tumor associated macrophages (TAMs) is an emerging strategy for cancer immunotherapy since it exerts anti-cancer effects based on modulating body immunity in tumor microenvironment (TME). This new strategy does not require high concentration of drugs to kill cancer cells directly and lessen tumor recurrence by creating unique immune memory for malignant cells. In this review, construction strategies of polysaccharide-based drug delivery system of three types of β-d -glucan including non-yeast and yeast β-d -glucans as well as hyper-branched β-d -glucan are discussed with reference to their branching characteristics and conformation. The applications of these β-d -glucans as nano-carrier for drug delivery targeting TAMs are also discussed.